2019
DOI: 10.1002/cncr.32521
|View full text |Cite
|
Sign up to set email alerts
|

Internet‐assisted cognitive behavioral intervention for targeted therapy–related fatigue in chronic myeloid leukemia: Results from a pilot randomized trial

Abstract: Background Fatigue is a common and disabling side effect of targeted therapies such as tyrosine kinase inhibitors (TKIs) used to treat chronic myeloid leukemia (CML). The goal of the current study was to conduct a pilot randomized trial of the first cognitive behavioral intervention developed for fatigue due to targeted therapy. Methods Patients with CML treated with a TKI who were reporting moderate to severe fatigue were recruited and randomized 2:1 to cognitive behavioral therapy for targeted therapy–relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Twenty‐three studies (Abrahams et al, 2017; Bantum et al, 2014; Boele et al, 2018; Foster et al, 2016; Freeman et al, 2015; Huberty et al, 2019; Jim et al, 2020; Kearney et al, 2009; Kubo et al, 2019; Ligibel et al, 2012; Ream et al, 2015; Ritterband et al, 2012; Shi et al, 2015; Smith et al, 2019; Somers et al, 2018; Spahrkas et al, 2020; Steel et al, 2016; Vallerand et al, 2018; van den Berg et al, 2015; Willems et al, 2017; Yun et al, 2012; Zachariae et al, 2018; Zhou et al, 2020) evaluated the effectiveness of eHealth interventions on CRF. The pooled result showed a small effect of eHealth interventions on CRF, and the improvement was not statistically significant (SMD = −0.16, 95% CI: −0.33 to 0.01, p = 0.07; I 2 = 79%, p < 0.00001) (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐three studies (Abrahams et al, 2017; Bantum et al, 2014; Boele et al, 2018; Foster et al, 2016; Freeman et al, 2015; Huberty et al, 2019; Jim et al, 2020; Kearney et al, 2009; Kubo et al, 2019; Ligibel et al, 2012; Ream et al, 2015; Ritterband et al, 2012; Shi et al, 2015; Smith et al, 2019; Somers et al, 2018; Spahrkas et al, 2020; Steel et al, 2016; Vallerand et al, 2018; van den Berg et al, 2015; Willems et al, 2017; Yun et al, 2012; Zachariae et al, 2018; Zhou et al, 2020) evaluated the effectiveness of eHealth interventions on CRF. The pooled result showed a small effect of eHealth interventions on CRF, and the improvement was not statistically significant (SMD = −0.16, 95% CI: −0.33 to 0.01, p = 0.07; I 2 = 79%, p < 0.00001) (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…The online delivery of CBT has several advantages over face-to-face delivery: (1) it ensures therapy continuation despite preventive public health measures, (2) the intervention is easily accessible, (3) it reduces patient burden as it saves time and costs to travel to the treatment centre and (4) for therapists, less time investment is needed which increases treatment capacity [ 27 , 29 ]. It has been shown that CBT interventions for severe fatigue can be successfully implemented in other countries and health care systems [ 88 , 89 ]. These advantages would ensure that the intervention can be readily implemented, reaching a large group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…For metastatic GIST patients in a stable phase who are being treated with TKI inhibitors, such an app-based tool might be of interest if psychosocial face-to-face intervention is not feasible. In addition, two studies in chronic myeloid leukemia patients on TKIs showed that cognitive behavioural therapy improved qualitative level of functioning and coping with treatment-related fatigue [ 43 , 44 ]. The translational value for GIST patients warrants further studies.…”
Section: Discussionmentioning
confidence: 99%